Marketing Strategy And Comonication Of Islamic Educational Institutions - Ansisca; A. Hanief Zayyadi; Aishmah Naily Fauziyah; Choirotul Maghfiroh; Farosa Nuralinda (Penerbit Hellow Pustaka, 2025)
This study aims to analyze the marketing strategies and communication practices implemented by Islamic educational institutions to enhance competitiveness and attract public interest. Using a qualitative approach and case study method, the research explores marketing practices in several Islamic schools through observation, in-depth interviews, and document analysis. The findings reveal that Islamic educational institutions have begun to adopt various modern marketing strategies combined with Islamic values, such as faith-based branding, the use of social media, personal approaches to parents, and strengthening institutional image through social and religious activities. Effective marketing communication—both verbal and non-verbal—successfully shapes positive public perception and expands the promotional reach of the institutions. The study concludes that the success of marketing efforts in Islamic educational institutions is highly influenced by the synergy between adaptive strategies and consistent, value-based communication. This research provides important insights into the dynamics of marketing in faith-based educational institutions in the digital era.